JAK inhibitors: an evidence-based choice of the most appropriate molecule - Antonioli, Luca; Armuzzi, Alessandro; Fantini, Massimo C.; Fornai, Matteo (Frontiers in Pharmacology, 2024)
Janus kinase inhibitors (JAKis) represent a fundamental therapeutic tool for the treatment of patients with immune-mediated inflammatory diseases. Although JAKis are often considered a homogeneous class of drugs whose members are thought to be largely interchangeable, there are significant differences in their efficacy and safety profiles. This narrative review analyzes the pharmacokinetic and pharmacodynamic differences among JAKIs, highlighting their clinical relevance based on the most recent available evidence. The article aims to provide rheumatologists, gastroenterologists and dermatologists with practical guidance for choosing the most appropriate JAKi for each patient, given the lack of evidence-based recommendations on this topic, to improve clinical outcomes. Due to its preferential action on JAK1, intestinal metabolization and proven absence of impact on male fertility, filgotinib may be characterized by an improved benefit/risk ratio compared with other less selective JAKis.